Efficient distributed reconfiguration for binary trees on Diogenes model - Sha, E.H.-M.; Chao, L.-F. (IEEE Annual Phoenix Conference on Computers and Communications, 11th, 1992, 1992)
The Diogenes model is a fault-tolerant model for many interconnection networks. The authors analyze a distributed reconfiguration algorithm for binary-tree structures based on this model. After a nonleaf node n in a binary tree has failed, the damage effect is minimized by substituting a leaf for n. The number of processing elements and the communication cost involved in the reconfiguration process are analyzed in the worst case and the average case. Several measures are defined for analyzing the performance of reconfigurable algorithms. It is shown that the reconfiguration algorithm can make the binary-tree structure become expected-case locally reconfigurable but not locally reconfigurable. By modifying the original Diogenes construction, the reconfiguration algorithm can achieve local reconfigurability. The performance analysis is presented.< >